EFL Teaching Methodological Practices in Cali - Chaves Orlando; Hernández Fanny (Universidad Nacional de Colombia, 2013)
In this article we aim at showing partial results of a study about the profiles of English as a Foreign Language (EFL) teachers in both public and private primary and secondary strata 1-4 schools in Cali, Colombia. Teachers' methodological approaches and practices are described and analyzed from a sample of 220 teachers. Information was gathered from surveys, interviews and institutional documents. The quantitative information was processed with the Statistical Package for the Social Sciences and Excel while the qualitative information (from a survey and focal interviews) was analyzed hermeneutically. An analysis grid was used for the examination of institutional documents (area planning, syllabi, and didactic materials). Teachers' methodology (approaches/methods), lessons, activities, objectives, curricula, syllabi and evaluation are analyzed in the light of literature in the field. Finally, we discuss the implications of methodological approaches. En este artículo se presentan los resultados parciales de una investigación sobre los perfiles de los profesores de inglés como lengua extranjera que enseñan en colegios de educación básica primaria y secundaria, públicos y privados, de estratos 1 a 4 en Cali, Colombia. Se describen y analizan sus enfoques y prácticas metodológicas a partir de una muestra de 220 docentes. Se obtuvo información cualitativa y cuantitativa por medio de encuestas, entrevistas y documentos institucionales. La información cuantitativa se procesó con el software Statistical Package for Social Sciences y Excel, mientras que la información cualitativa se analizó hermenéuticamente. Se usó una rejilla de análisis para el examen de los documentos institucionales (planes de área, programas, y materiales didácticos). La metodología (enfoques/métodos), clases, actividades, objetivos, currículo, programas y evaluación se analizan a partir de la literatura especializada en el campo. Finalmente, se discuten las implicaciones de estos enfoques metodológicos.